2019
DOI: 10.3390/en12061045
|View full text |Cite
|
Sign up to set email alerts
|

Fixing Efficiency Values by Unfixing Compressor Speed: Dynamic Test Method for Heat Pumps

Abstract: The growing market penetration of heat pumps indicates the need for a performance test method that better reflects the dynamic behavior of heat pumps. In this contribution, we developed and implemented a dynamic test method for the evaluation of the seasonal performance of heat pumps by means of laboratory testing. Current standards force the heat pump control inactive by fixing the compressor speed. In contrast, during dynamic testing, the compressor runs unfixed while the heat pump is subjected to a temperat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Furthermore, the possibility of working at partial load was also considered. Several studies of HTHPs found in the literature [26][27][28][29][30] have shown that variable speed compressors present an increase in the coefficient of performance (COP) (defined as the ratio between the sum of latent and…”
Section: Modelling Of the Hthp And Orcmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the possibility of working at partial load was also considered. Several studies of HTHPs found in the literature [26][27][28][29][30] have shown that variable speed compressors present an increase in the coefficient of performance (COP) (defined as the ratio between the sum of latent and…”
Section: Modelling Of the Hthp And Orcmentioning
confidence: 99%
“…Furthermore, the possibility of working at partial load was also considered. Several studies of HTHPs found in the literature [26][27][28][29][30] have shown that variable speed compressors present an increase in the coefficient of performance (COP) (defined as the ratio between the sum of latent and sensible power heat produced and the electrical energy needed at the HTHP's compressor) when working at a partial load (especially between 30% and 50%). This is due to the fact that the mass flow rate also decreases, leading to a lower temperature lift between the evaporator and condenser, which reduces the pressure ratio [26].…”
Section: Modelling Of the Hthp And Orcmentioning
confidence: 99%